CONCEPT OF A JOINT STOCK COMPANY - Belovski, Vojo (Journal of process management and new technologies, 2017)
Companies are classified in two separate groups. One is the so-called personal type of companies, the other is the capital type. Companies of capital are those whose essence is joining of capital. Unlike companies of capital, where for the work of the company it is important to raise capital from various sources, regardless of the fact who the persons giving it are, the personal type of companies are based on persons who make up that company. Out of the companies provided by the laws on companies only two are pure types of companies of capital, i.e. companies of persons without any qualities that are attributed to the other type of companies. A joint stock company has, solely, the characteristics of a company of capital. The prototype of a personal company type is the public trade company. A company is, in fact, a union of those persons. In the company of persons each partner agrees to participate in the company, valuing the personality of the other stakeholders (intuitipersone).